ENHANCING STUDENTS’ MATHEMATICAL REPRESENTATION ABILITY THROUGH MATHEMATICS LEARNING - Azmidar Azmidar; Hartina Husan (Hipotenusa Journal of Research Mathematics Education (HJRME), 2022)
Several previous researchers indicated that students’ mathematical representation ability is still low because most of them have perceived that mathematics is very difficult, boring, not very practical, and has many abstract theorems that are very hard to understand. Another cause is the teaching and learning process used, which is mechanistic without considering students’ needs. Learning is more known as the process of transferring knowledge to students. Let students construct their knowledge with the physical and mental reflection that is done by activity in the new knowledge. This article is a literature study. This article aims to examine the Concrete-Pictorial-Abstract approach theoretically to improve students’ mathematics representation ability. The conclusion of this literature study is the Concrete-Pictorial-Abstract approach can be used as an alternative to improve students’ mathematical representation ability.